Betrayal of trust - Jance, Judith A. (Jance, Judith A. J. P. Beaumont mysteries, 2011)
Seattle P.I. J. P. Beaumont uncovers a crime that has a devastating effect on two troubled teens and becomes even more of a firestorm when it reaches into the halls of state government.